2021
DOI: 10.1002/aoc.6253
|View full text |Cite
|
Sign up to set email alerts
|

CO2 hydrogenation to C5+ hydrocarbons over K‐promoted Fe/CNT catalyst: Effect of potassium on structure–activity relationship

Abstract: Developing efficient catalysts for direct CO2 hydrogenation to fuel hydrocarbons is of great significance for the effective utilization of CO2, and C5+ selectivity is one critical indicator for the process economics. In this work, a series of K‐promoted Fe/CNT catalysts were prepared by the co‐impregnation method, and their catalytic performance for CO2 hydrogenation was studied in a slurry‐bed reactor. As a result, CO2 conversion and C5+ selectivity showed positive correlation with the increase of K/Fe ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 56 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…As such, a compromise between chemisorption, reduction, and carburization may need to be considered upon K decoration to modify the surface C:H in favor of carburization and C-C coupling. [110] Recent work by Yang et al suggested that the Fe binding energy in Fe 5 C 2 can be influenced by the alkaline species added (Li, Na, K, Rb, or Cs) and the loading, the extent of which could be correlated to the Allen electronegativity scale. A more electronegative species with lower-energy valence electrons could better enhance CO 2 adsorption and dissociation, while decreasing the adsorption strength of olefins.…”
Section: Promoter Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, a compromise between chemisorption, reduction, and carburization may need to be considered upon K decoration to modify the surface C:H in favor of carburization and C-C coupling. [110] Recent work by Yang et al suggested that the Fe binding energy in Fe 5 C 2 can be influenced by the alkaline species added (Li, Na, K, Rb, or Cs) and the loading, the extent of which could be correlated to the Allen electronegativity scale. A more electronegative species with lower-energy valence electrons could better enhance CO 2 adsorption and dissociation, while decreasing the adsorption strength of olefins.…”
Section: Promoter Speciesmentioning
confidence: 99%
“…As such, a compromise between chemisorption, reduction, and carburization may need to be considered upon K decoration to modify the surface C:H in favor of carburization and C–C coupling. [ 110 ]…”
Section: Catalyst Designmentioning
confidence: 99%
“…31 Specically, magnetite and iron carbide serve as the active phases for these reactions, respectively. [32][33][34][35] In our previous research work, we optimized the catalytic system composition through utilization of metalorganic framework (MOF) as a sacricial template to form a carbon-supported iron nanoparticles for converting carbon dioxide into valuable hydrocarbons. 36 This approach deviated from the conventional usage of inorganic supports like Al 2 O 3 , SiO 2 , and TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been devoted on the carbon capture, utilization, and storage (CCUS). Catalytic transformation of CO 2 into high-value chemicals, [2] methane, [3,4] methanol, [5,6] olefins, [7][8][9] and C 5þ hydrocarbons [10,11] is an ideal method to reduce CO 2 emissions. Among these routes, CO 2 hydrogenation to light hydrocarbons including alkanes and olefins is one of the most promising routes.Most of the CO 2 hydrogenation reactions were conducted by the electrocatalysis, photocatalysis, or thermal-catalysis processes.…”
mentioning
confidence: 99%